2022
DOI: 10.3389/fimmu.2022.765284
|View full text |Cite
|
Sign up to set email alerts
|

Efficient DNA Repair Mitigates Replication Stress Resulting in Less Immunogenic Cytosolic DNA in Radioresistant Breast Cancer Stem Cells

Abstract: Cancer stem cells (CSCs) are a major cause of tumor therapy failure. This is mainly attributed to increased DNA repair capacity and immune escape. Recent studies have shown that functional DNA repair via homologous recombination (HR) prevents radiation-induced accumulation of DNA in the cytoplasm, thereby inhibiting the intracellular immune response. However, it is unclear whether CSCs can suppress radiation-induced cytoplasmic dsDNA formation. Here, we show that the increased radioresistance of ALDH1-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
(99 reference statements)
1
10
0
Order By: Relevance
“…It has been reported that metastatic spread to the brain has an impact on radioresistance of MDA-MB-231 cells as shown by a clonogenic assay (34) which could be due to the influence of the brain microenvironment on gene expression patterns of the tumor cells, as also indicated by the findings of Park et al (35). Radioresistance was verified as previously described (27). The clonogenic survival (Figure 1) confirms that the RR clones have enhanced potential to still form colonies after radiation exposure compared the non-RR clones.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been reported that metastatic spread to the brain has an impact on radioresistance of MDA-MB-231 cells as shown by a clonogenic assay (34) which could be due to the influence of the brain microenvironment on gene expression patterns of the tumor cells, as also indicated by the findings of Park et al (35). Radioresistance was verified as previously described (27). The clonogenic survival (Figure 1) confirms that the RR clones have enhanced potential to still form colonies after radiation exposure compared the non-RR clones.…”
Section: Discussionsupporting
confidence: 70%
“…Four different human MDA-MB-231 cell lines with differences in radioresistance (according to their behaviour in the clonogenic assays) were investigated ( 27 ). Besides the wildtype (WT), a brain-metastasizing (BR) clone was used.…”
Section: Methodsmentioning
confidence: 99%
“…RS has been highlighted as a hallmark of malignant tumor radiosensitivity (6,14). Impaired responses to RS sensitize tumors to radiation (15), highlighting the importance of RSaimed therapy for radiation treatment.…”
mentioning
confidence: 99%
“…BCSCs isolated from triple-negative cell lines showed elevated expression of the MRN complex component RAD50, leading to enhanced HR activity [ 139 ]. Similarly, BCSCs derived from the ER + MCF-7 cell line demonstrated reduced sensitivity to IR treatment which was correlated to increased HR activity as measured by the I-Sce/GFP reporter assay [ 140 ]. Interestingly, these BCSCs also showed a more effective RS response because hydroxyurea promoted replication fork degradation and DNA damage more extensively in the bulk MCF-7 population [ 140 ].…”
Section: Dna Damage Repair In Cscs and Therapeutic Interventionmentioning
confidence: 99%
“…Similarly, BCSCs derived from the ER + MCF-7 cell line demonstrated reduced sensitivity to IR treatment which was correlated to increased HR activity as measured by the I-Sce/GFP reporter assay [ 140 ]. Interestingly, these BCSCs also showed a more effective RS response because hydroxyurea promoted replication fork degradation and DNA damage more extensively in the bulk MCF-7 population [ 140 ]. Supporting this, gene expression profiling of BCSCs from PDX breast models identified an enriched RS response gene signature compared to bulk tumour cells [ 141 ].…”
Section: Dna Damage Repair In Cscs and Therapeutic Interventionmentioning
confidence: 99%